Local instructional theory of probability topics based on realistic mathematics education for eight-grade students - Armiati; Fauzan, Ahmad; Harisman, Yulyanti; Sya’bani, Febrina (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2022)
This study examines the development of learning designs based on Realistic Mathematics Education (RME) on the probability topic at the eighth-grade junior high school level. Probability abounds in everyday life, and the RME approach is believed to develop students’ mathematical communication skills. This learning design development used the Plomp model combined with Gravemeijer and Cobb model. The research phase includes preliminary research, prototyping phase, and assessment phase. The products of this research are a valid, practice, and effective Local Instructional Theory (LIT) and teacher and student books. The results showed that the students who participated in learning using RME-based designs could determine the concept of probability and effectively improve students’ mathematical communication skills.